A high-sensitivity optical device for the early monitoring of plant pathogen attack via the in vivo detection of ROS bursts - Zeng, Lizhang; Zhou, Jun; Li, Bo; Xing, Da (Frontiers in Plant Science, 2015)
Biotic stressors, especially pathogenic microorganisms, are rather difficult to detect. In plants, one of the earliest cellular responses following pathogen infection is the production of reactive oxygen species (ROS). In this study, a novel optical device for the early monitoring of Pseudomonas attack was developed; this device measures the ROS level via oxidation-sensitive 2’, 7’-dichlorodihydrofluorescein diacetate (H2DCFDA)-mediated fluorescence, which could provide early monitoring of attacks by a range of plant pathogen; ROS bursts were detected in vivo in Arabidopsis thaliana with higher sensitivity and accuracy than those of a commercial luminescence spectrophotometer. Additionally, the DCF fluorescence truly reflected early changes in the ROS level, as indicated by an evaluation of the H2O2 content and the tight association between the ROS and Pseudomonas concentration. Moreover, compared with traditional methods for detecting plant pathogen attacks based on physiological and biochemical measurements, our proposed technique also offers significant advantages, such as low cost, simplicity, convenient operation and quick turnaround. These results therefore suggest that the proposed optical device could be useful for the rapid monitoring of attacks by plant pathogen and yield results considerably earlier than the appearance of visual changes in plant morphology or growth.